Condemnation of Patriarchal Preeminence in Sula - Pokharel, Bishnu Prasad (Advances in Social Sciences Research Journal, 2020)
Published in 1973, the black writer Toni Morrison’s novel Sula narrates a journey of the main protagonist Sula, who after learning that male chauvinist forces have perennially stunted her spontaneous growth, decides to protest and rebel against those very forces. This article analyzes the novel from feminist lens to explore how far the main protagonist Sula denies hierarchical order of male superiority. The paper provides critical remarks about Sula, then employs feminism as a theoretical tool, and applies the same theory to analyze the text to present Sula’s resistance.